2016
DOI: 10.1186/s13287-016-0379-z
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of responders to autologous bone marrow cell therapy for no-option critical limb ischemia

Abstract: BackgroundThe present study investigated factors associated with therapeutic benefits after autologous bone marrow cell (BMC) therapy in patients with “no-option” critical limb ischemia (CLI).Methods and resultsSixty-two patients with advanced CLI (Rutherford category 5 or 6) not eligible for revascularization were randomized to treatment with 40 ml of autologous BMCs (SmartPreP2) by local intramuscular (n = 32) or intra-arterial (n = 30) application. The primary endpoint was limb salvage and wound healing at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 34 publications
(39 reference statements)
4
30
0
Order By: Relevance
“…The benefit of cell therapy on limb salvage has been proven by several randomized controlled trials [14,22,23] and metaanalyses in those with and without diabetes [24,25]. These studies showed lower amputation rates in the cell therapy groups compared to standard treatment or placebo, while no significant differences in pain scores and ischaemic variables were observed in the study by Pignon et al [23] in people who underwent bone marrow autograft for limb ischaemia.…”
Section: Discussionmentioning
confidence: 99%
“…The benefit of cell therapy on limb salvage has been proven by several randomized controlled trials [14,22,23] and metaanalyses in those with and without diabetes [24,25]. These studies showed lower amputation rates in the cell therapy groups compared to standard treatment or placebo, while no significant differences in pain scores and ischaemic variables were observed in the study by Pignon et al [23] in people who underwent bone marrow autograft for limb ischaemia.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Dong et al, using purified CD34+ cells in CLI patients, did not report a correlation between improvement of clinical outcomes and low, medium, or high doses of injected CD34+ cells 37 . On the other hand, Madaric et al investigated factors associated with clinical benefits of ACT in patients with no-option CLI and discovered that the number of injected CD34+ cells was an independent predictor of limb salvage and wound healing 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Updated in 2017, a similar meta‐analysis by Rigatto et al, included 19 RCT (837 CLI patients) concluded cell therapy modestly reduced the risk of amputation by 37%, improved amputation free survival by 18%, and improved wound healing by 59% . Finally, in an uncontrolled study, Madaric et al , analyzed the outcomes of 55 patients transplanted with BM MNC and concluded that responding patients with limb salvage and wound healing (33 of 55) at 1 year were transplanted with significantly higher MNC ( p = .032) and CD34+ cell dose ( p = .001) compared with nonresponders that required limb amputation (22 of 55). Therefore, in contrast to cell therapy trials for heart disease , the benefits of cell therapy for CLI are clearly evident, and considering up to 50% of CLI patients may not be candidates for revascularization therapies, cell therapy should be considered safe option for improving ABI, rest pain, and ulcer healing.…”
Section: What Has Gone Wrong and What Can We Do Better?mentioning
confidence: 99%